NANOTECHNOLOGY-BASED COSMECEUTICALS: A REVIEW - DUARAH, SANJUKTA; PUJARI, KUNAL; DURAI, RAMYA DEVI; NARAYANAN, VEDHA HARI B. (International Journal of Applied Pharmaceutics, 2016)
Nanotechnology signifies the evolving area of research and development, concerned in delivering innovative solutions to increase the efficacy of a product. In recent times, application of nanotechnology is rising in the arena of cosmeceuticals and seems to be promising in overcoming certain drawbacks associated with the traditional products. The nanotechnology-based delivery techniques have proved to offer advantages of greater stability, higher efficacy and have also been reported to show prolonged effects. Nanoparticles are also proficient in modifying the flux, targeting the drug to the location, tailoring the size of drug and in making the stratum corneum permeable in a selective manner. The rapid evolution of nanotechnology has given rise to great aspirations; however there are certain concerns still, regarding the possible hazards of nanoparticles to the human health, which could be neglected because of their less significant toxicity. This review gives a brief overview of the various novel nano-carriers for cosmeceuticals like nanoemulsions, liposomes, solid lipid nanoparticles(SLNs), dendrimers, inorganic nanoparticles, nanocrystals, etc. Safety of nanoparticles use and also the different routes of exposure to the nanoparticles have been discussed here. Keywords: Cosmeceutical, Nanotechnology, Stratum corneum, Nano-carrier, Hazard.